Synthesis and characterization of polyimides and co-polyimides having pendant benzoic acid moiety - Kulkarni, M; Kothawade, S; Arabale, G.; Wagh, D; Vijayamohanan, K; Kulkarni, RA; Vernekar, SP (Polymer, 2005)
A novel diamine monomer, 2,4-diamino-4'-carboxy diphenyl ether had been synthesized. Several polyimides were prepared by reacting this diamine with commercially available dianhydrides, such as benzophenone tetracarboxylic acid dianhydride (BTDA), 4,4'bis{hexafluoroisopropylidene his (phthalic anhydride)} (6-FDA), oxydiphthalic anhydride (ODPA) and 3,3',4,4'-biphenyltetracarboxylic acid dianhydride (BPDA). Furthermore, copolymers from the resulting diamine and oxydianiline (ODA) with 6 FDA were also synthesized. The inherent viscosities of the polymers were 0.42-0.67 dl g(-1). The polymers have good solubility in polar aprotic solvents, high thermal stability up to 410 &DEG; C in nitrogen and high glass transition temperatures (T-g) ranging from 260-330 &DEG; C. These polymers formed tough flexible films by solution casting. © 2005 Elsevier Ltd. All rights reserved.
Keywords: co-polyimides; diamine with pendant benzoic acid; polyimides with pendant benzoic acid